Pengaruh Harga, Produk, Promosi dan Lokasi terhadap Keputusan Pembelian Rumah pada Perumahan Satria Nusantara Kabupaten Konawe (Studi Kasus Pada Perumahan Satria Nusantara Kabupaten Konawe) - Kelana, Irham Natsir; Raldianingrat, Welis (Jurnal Ilmiah Dikdaya, 2022)
This study aims 1) to determine the effect of price on home purchase decisions at Satria Nusantara Housing, Konawe Regency. 2) to determine the effect of the product on the decision to purchase a house at the Satria Nusantara Housing, Konawe Regency. 3) to determine the effect of promotion on home buying decisions at the Satria Nusantara Housing, Konawe Regency. 4) to determine the effect of location on the decision to buy a house at the Satria Nusantara Housing, Konawe Regency. The population used in this study are consumers who buy houses at the Satria Nusantara Housing, Konawe Regency with a total of 67 respondents. The method used in sampling is the Slovin technique formula and the analysis method using multiple linear regression using the SPSS application. The results of this study indicate that the price has a significant effect on the decision to purchase a house at the Satria Nusantara Housing, Konawe Regency. The product has a significant effect on the decision to buy a house at the Satria Nusantara Housing, Konawe Regency. Promotion has a significant effect on home buying decisions at the Satria Nusantara Housing, Konawe Regency. Location has a significant effect on home purchase decisions at the Satria Nusantara Housing, Konawe Regency.